Hasten and Competing in Good Deeds in Light of the Glorious Quran - Al-ABDALI, KHALID MOHAMMED SALIM (Journal of Islamic Sciences, 2019)
This study aims to unveil a Quranic truth, that is, the depiction of prophets, messengers and the pious as they hasten in doing good deeds relentlessly and persistently. They are restless in doing the good deeds and never astray the scope of good deeds. The researcher indicated in his study that the Quran never characterized the pious as they “hasten toward good deeds. This is due to the fact that “hasten in something / compete” differs from “hasten toward something / contest” in the way the latter connotes that the person is out of the scope. Thus, there must be a differentiation between “hasten in” and “hasten toward” as well as between “compete and contest”. This is one of precise particulars and mysteries of the Quran that should be clarified. The researcher used the inductive method of the texts of the Qur'an under discussion. He relied on the analytical method by examining the verses and clarifying their linguistic and legislative inimitability, and shedding the light of the magnificence of the tropes of the Qur'an, as Allah placed every verse in its proper position. Moreover, the location of each word shows the extent of the divine wisdom in it. Through reflecting in the verses of the Qur'an, these facts and particulars are revealed. The researcher based on the critical approach in understanding the references of the verses refer. The most prominent outcome of this study are as follows:1- The precision of the words “hasten” and “compete” and their position in the Quran which is considered as linguistic inimitability.2- The Quran stated the phrase “hasten in doing good deeds” rather “hasten toward doing good deeds”.3- Differentiating between the verbs “hasten and hurry” and between “compete and contest” clarifying the precision of the Quranic phrasing.
Keywords: Hasten; compete; good deeds; reflecting; wisdom